First Report of Cladosporium dominicanum Zalar, de Hoog & Gunde-Cim. Infecting Whitefly on Ornamental Plants in Bali, Indonesia - Sudiarta, I Putu; Sugiarta, Dwi; Selangga, Dewa Gede Wiryangga; Wirya, Gusti Ngurah Alit Susanta; Gargita, I Wayan Diksa; Yuliadhi, Ketut Ayu; Klett, Katrina (Universitas Gadjah Mada, 2024)
As natural enemies, entomopathogenic fungi are essential for controlling certain plant pests, such as whitefly. Many types of entomopathogenic fungi can infect whiteflies, including those from the genera Aschersonia, Metarhizium, Beauveria, and Cladosporium. Currently, there is great interest in using entomopathogenic fungi as an environmentally friendly pest control in organic and sustainable agricultural systems. This study aimed to identify entomopathogenic fungus associated with whiteflies. Identification of entomopathogenic fungus was performed morphologically and molecularly using DNA barcoding with ITS-1 and ITS-4 as primers, in addition to sequencing and phylogenetic tree analysis. Whiteflies infected with entomopathogenic fungus were discovered on ornamental plants (Premna serratifolia, Ficus religiosa, and Ficus rumphii) in Denpasar, Bali, Indonesia from January to March 2023. We found that samples from the field had mycelium that was unbranched or sparingly branched with solitary conidiophores arising terminally from ascending hyphae or laterally from plagiotropous hyphae. Samples from PDA media had ramoconidia with darkened septa, straight and conidia in long branched chains, branching in all directions, conidia were obovoid, ovoid to limoniform. The fungal colonies had the characteristics of being grey-olivaceous, olivaceous-black, and the margins were grey-livaceous to white, gray olivaceous in colony center due to abundant sporulation. In addition, based on the BLAST nucleotide sequence from NCBI GenBank, the insect pathogen phylogenetic tree found in Denpasar, Bali, is in the same clade as Cladosporium dominicanum strain SCAU014, accession number KY827344.1. Based on morphological and molecular analysis the fungus that infects whiteflies on ornamental plants is C. dominicanum.